2010
DOI: 10.1073/pnas.1007909107
|View full text |Cite
|
Sign up to set email alerts
|

12/15-lipoxygenase–derived lipid peroxides control receptor tyrosine kinase signaling through oxidation of protein tyrosine phosphatases

Abstract: Protein tyrosine phosphatases (PTPs) are regulated through reversible oxidation of the active-site cysteine. Previous studies have implied soluble reactive oxygen species (ROS), like H 2 O 2 , as the mediators of PTP oxidation. The potential role(s) of peroxidized lipids in PTP oxidation have not been described. This study demonstrates that increases in cellular lipid peroxides, induced by disruption of glutathione peroxidase 4, induce cellular PTP oxidation and reduce the activity of PDGF receptor targeting P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 49 publications
3
62
0
1
Order By: Relevance
“…This concurs with reports showing 12/15-lipoxygenase-catalzed lipid peroxidation to modulate intracellular signaling, i.e. tyrosine phosphatase activity (45). Our data point to 15(S)-HETE being involved in proinflammatory macrophage activation, although a much lower efficacy was observed compared with IL-4 pretreatment.…”
Section: Discussionsupporting
confidence: 74%
“…This concurs with reports showing 12/15-lipoxygenase-catalzed lipid peroxidation to modulate intracellular signaling, i.e. tyrosine phosphatase activity (45). Our data point to 15(S)-HETE being involved in proinflammatory macrophage activation, although a much lower efficacy was observed compared with IL-4 pretreatment.…”
Section: Discussionsupporting
confidence: 74%
“…Due to reversible oxidation of the Cys residue in the active site of PTPs, H 2 O 2 has been shown to inhibit their function. A recent study demonstrated that, in addition to H 2 O 2 , PTPs are also subject to inactivation by lipid hydroperoxides (69). Therefore, similar to GPx1 and peroxiredoxin II (PrxII), which regulate PTPs by modulating levels of H 2 O 2 , GPx4 may participate in the control of PTP proteins by degrading lipid hydroperoxides.…”
Section: Selenoprotein Functionmentioning
confidence: 99%
“…As just mentioned, the GPX1 and 3 play important roles in reducing H 2 O 2 to water, and Se status in immune cells can directly affect the half-life of this ROS. In addition, GPX4 educes phospholipid hydroperoxides, and this activity has recently been shown to regulate protein tyrosine phosphatase (PTP) signaling, particularly through Gpx4-mediated reduction of 12/15-lipoxygenase (45). Txnrd1 may indirectly regulate the downstream effects of H 2 O 2 by reducing disulfide bonds generated by H 2 O 2 in signaling molecules.…”
Section: Se and Redox Signaling In Immune Cellsmentioning
confidence: 99%
“…Oxidation of this Cys by H 2 O 2 inactivates the PTP, and reduction by GSH or TXN reverts the catalytic domain back to its active state (37,272). In addition to H 2 O 2 , phospholipid hydroperoxides can also oxidize signaling molecules at their active-site Cys residues (45).…”
Section: Se Levels Related To Calcium and Redox Signaling In Immunmentioning
confidence: 99%